Carbon-coated Single-phase Ti4O7 Nanoparticles as Electrocatalyst Support - Christina Wahyu Kartikowati; Aditya Farhan Arif; Osi Arutanti; Takashi Ogi (Universitas Pendidikan Indonesia, 2021)
The unique structure of Magnéli phases TiOx renders them effective for the electrochemical applications. This work demonstrates a synthesis of carbon-coated Magnéli phases TiOx (TiOx@C) nanoparticles from 3-aminophenol and rutile titania (TiO2) nanoparticles as a support for platinum (Pt) electrocatalyst. 3-aminophenol was polymerized and carbonized on the surface of TiO2 nanoparticles respectively in a microwave hydrothermal reactor and a tubular furnace. Reduction of the carbon-coated TiO2 (TiO2@C) into TiOx@C was performed in hydrogen atmosphere at 800-1050 °C. The carbon coating effectively prevented TiO2 nanoparticles from sintering, resulted in TiOx@C sizes from 50 to 100 nm. Single-phase Ti4O7 core, which has the highest theoretical electrical conductivity among the Magnéli phases, was obtained from reduction of TiO2@C at 1000 °C. for 10 min C/Ti4O7-supported Pt exhibited an electrochemical surface area of 46 m2 mgPt-1 at 15% Pt loading, slightly higher than that reported for commercial TKK electrocatalyst with 20% Pt loading (44.13 m2 mgPt-1).